Can social media data be used to evaluate the risk of human interactions during the COVID-19 pandemic?. (1st April 2021) - Li, Lingyao; Ma, Zihui; Lee, Hyesoo; Lee, Sanggyu
Abstract: The U.S. has taken multiple measures to contain the spread of COVID-19, including the implementation of lockdown orders and social distancing practices. Evaluating social distancing is critical since it reflects the risk of close human interactions. While questionnaire surveys or mobility data-based systems have provided valuable insights, social media data can contribute as an additional instrument to help monitor the risk of human interactions during the pandemic. For this reason, this study introduced a social media-based approach that quantifies the pro/anti-lockdown ratio as an indicator of the risk of human interactions. With the aid of natural language processing and machine learning techniques, this study classified the lockdown-related tweets and quantified the pro/anti-lockdown ratio for each state over time. The anti-lockdown ratio showed a moderate and negative correlation with the state-level social distancing index on a weekly basis, suggesting that people are more likely to travel out of the state where the higher anti-lockdown level is observed. The study further showed that the perception expressed on social media could reflect people's behaviors. The findings of the study are of significance for government agencies to assess the risk of close human interactions and to evaluate their policy effectiveness in the context of social distancing and lockdown. Highlights: Introduce a social media-based approach to evaluate the risk of human interactions across the U.S. Demonstrate the associations of pro/anti-lockdown ratio with reported COVID-19 infections. Illustrate a negative correlation between the anti-lockdown ratio and the social distancing index. Show that people from states with higher anti-lockdown ratio were more likely to travel outside.